ALGORITHM OF GUARANTEED-AND-ADAPTIVE CONTROL OF AEROSTATIC VEHICLE UNDER UNDETERMINED EXTERNAL TURBULENCES - Bogunenko, Nikolay; Radchenko, Yulia (Proceedings of National Aviation University (archive), 2014)
The article is devoted to the analysis of current information management systems and System WideInformation Management. The limitations of current systems and benefits of the new system were revealed. TheEuropean experience of System Wide Information Management implementation has been investigated in the scope ofUkrainian information management system.